Aprendizagem ética relacionada ao meio ambiente : concepção dos profissionais da educação da escola pública de Garanhuns/PE - Melo, Josevaldo Araújo de (2012)
The study defines and discusses the concepts relating to ethics, learning process and environment, taken as empirical base the educational professionals of the public school of Garanhuns/PE, aiming to learn the concepts of education professionals in relation to learning ethics related to the environment. This was achieved with the application of questionnaires, which were categorized on the basis of the singularities of the information and fragments of concepts, definitions, strategies and factors promoters of significant learning experiences. In order to this achievement, we obtained as respondents 92 (ninety-two) education professionals that had partaken of courses of specialisations promoted in locus at the University of Pernambuco - Campus Garanhuns. The colected data were analyzed qualitatively based on the description and informal conversations. The arguments presented are essentially natural part of their perception about the environmental issues and their actions in the public school. However, differences are in logical connections between the evidence and interpretation of the respondents. The logical connections are defined in terms of tropes of language: similarity, causal relations, use of metaphor and relations of the representations of the thematic learning ethics. Such connections delimit contexts in which quantities and qualities work as a dynamic part and with prospects of changes of attitudes in relation to significant learning experiences. So, our choices for the trial in relation to fragments presented by education professionals as being essential for the formation of the future citizen, supporting the idea that the evidence presented in this study can be considered as a marker for changes in political-pedagogical projects of public schools in Garanhuns/PE